Legal Protection Efforts for Taxpayers in the Tax Dispute Resolution Mechanism - Nugroho, Hizkia Ivan; Lestari, Novianti; Rasji, Rasji (CV. Rayyan Dwi Bharata, 2023)
Tax is one of the income of the state treasury as an instrument of development with the ultimate goal of people's welfare and prosperity. Rather than that, paying taxes is a mandatory payment for all Indonesian citizens which is coercive by using a self-assessment system that focuses on taxpayer awareness in determining the amount of tax owed to taxpayers. Over time, many tax disputes have occurred in Indonesia. A tax dispute is a problem that arises as a result of a discrepancy in terms of tax collection with tax regulations, causing a dispute regarding the implementation of tax regulations. Legal protection for taxpayers in the settlement of tax disputes based on the taxation law also serves as the basis and legal basis for the parties to resolve tax disputes. Then the parties involved in the tax dispute are the taxpayer and the Directorate General of Taxes (DGT). With the existence of tax disputes, efforts to protect tax law arise which can be resolved by various dispute resolution mechanisms, namely filing lawsuits, appeals, arbitration, review, and arbitration. As, the role of institutions such as tax courts and arbitration bodies in providing legal protection to taxpayers in tax disputes.